Creating an environment for successful projects - Graham, Robert J., 1946-; Englund, Randall L. (Berrett-Koehler Publishers, 2019)
Now in its third edition, this project management classic has been updated with an array of field-tested tools to help upper management ensure the success of projects within organizations. /> />For over twenty years, Creating an Environment for Successful Projects has been a staple for upper managers who want to help projects succeed. This new edition includes case studies from companies that have successfully applied the approach, along with practical tools such as templates, surveys, and benchmark reports for savvy leaders who want to ensure project success throughout their organizations. The insights in this book will help management speed projects along instead of getting in their way. All too often, well-intentioned managers put roadblocks in the team's way instead of empowering them with the tools they need to succeed. This approach to project environments, grounded in decades of research and practice, will help you make your organization the most project-friendly it's ever been. /> />Organizational changes rarely work unless upper management is heavily involved. Although project managers are most closely responsible for the success of projects, upper managers are the ones who ultimately create an environment that supports those projects. The way upper managers define, structure, and act toward projects has an important effect on the success or failure of those projects and, consequently, the success or failure of the organization. This book helps all managers understand the need for project management changes and shows how to develop project management as an organizational practice.